x+2/x+3=x-1/x+1. Solve the following equation for x. The solution is ?

Thank you for your help have worked this problem and ones like this for hours can't get the right answer:)

2 answers

x + 2/x + 3 = x - 1/x + 1
It's usually helpful to get rid of denominators, so multiply both sides by x
x^2 + 2 + 3x = x^2 - 1 + x
subtract x^2 from both sides
2 + 3x = -1 + x
collect like terms
2x = -3
So, x = ?
Kay, can you see how important it is to use brackets to correctly show your equation.

Quidditch solved your equation correctly according to the way you typed it, but I have a suspicion that, since you worked on this "for hours", that you probably meant,
(x+2)/(x+3) = (x-1)/(x+1)

if so, then .... cross-multiply

(x+2)(x+1) = (x+3)(x-1)

take it from there, (Igot x = -5)